5-Amino-5-deoxy-2-C-hydroxymethyl-2,3-O-isopropylidene-l-lyxono-1,5-lact am - Simone, M; Fleet, G; Bream, R; Watkin, D (2007)
The relative configuration of the title compound, C9H14NO5, formed by catalytic hydrogenation of an azido-lactone, has been established by X-ray crystallographic analysis. The absolute configuration was determined by the use of 2,3-O-isopropyl-idene-l-lyxono-1,4-lactone as the carbohydrate starting material. © International Union of Crystallography 2007.